The Role of The Credit-Module System in Higher Education System in Uzbekistan - Shakhnoza Tadjimova (Indonesian Journal Publisher, 2025)
This article explores the implementation and impact of the credit-modular system (ECTS) in the higher education sector of Uzbekistan. The study is motivated by recent reforms aimed at improving educational quality, student autonomy, and alignment with international standards. Based on document analysis, academic literature, and empirical data gathered through interviews and surveys at a technical university, the article assesses how the CMS influences teaching and learning processes. The research reveals that ECTS encourages a shift from teacher-centered to student-centered learning, promoting independence, critical thinking, and time management. A comparative table outlines the fundamental differences between the traditional and modular systems in terms of flexibility, curriculum design, and assessment. Survey data from students and teachers confirm both the benefits and initial challenges of transitioning to the CMS